Integrating combat effectiveness disciplines into the aircraft conceptual/preliminary design phase - Al-Ahmed, S. M. (Cranfield University, 1996)
An assessment methodology has been developed for - use during the conceptual/preliminary design phase to quantify the effectiveness of newly designed aircraft. The effectiveness is measured by a squadron Sortie Generation Rate (SGR). Key elements of this methodology were the establishment of link parameters between design synthesis and the main effectiveness disciplines. These were Reliability and Maintainability (R&M), Survivability / Vulnerability and Acquisition Cost. A programmable solid modeller was used to create a solid CAD assembly of the aircraft critical components. A ray tracing technique has been used to develop an interactive vulnerability assessment tool. A Mission Simulation Model (MSM) has been developed which typically simulates the operation of a squadron of aircraft and gives the operational activities such as flying sorties and maintenance actions. The methodology has been validated based on real data from recent conflicts. The application aspects of the methodology have been demonstrated by quantifying the effectiveness of two recent combat aircraft.